Characteristics of peripheral immune response induced by large-vessel occlusion in patients with acute ischemic stroke - Ling Ma; Bin Sun; Chenliu Fan; Juan Xiao; Maomao Geng; Jie Liu; Runze Jiang; Yang Jiang; Dianwei Liu (Frontiers in Neurology)
IntroductionDespite improvements in the treatment of acute ischemic stroke (AIS), some patients still suffer from functional impairments, indicating the poor understanding of pathophysiologic process of AIS. Inflammation plays an important role in the pathophysiology of AIS. The purpose of the study was to investigate the peripheral inflammation in different subtypes of AIS.MethodsHere, retrospective data from AIS with large vessel occlusion (LVO) and small vessel occlusion (SVO), and healthy controls, were initially analyzed. Then, flow cytometry was performed to evaluate the levels of peripheral naïve and memory T-cells. Finally, we characterized the T cell receptors (TCR) repertoire using high-throughput sequencing.ResultsElevated levels of leukocytes, neutrophils, and neutrophil-to-lymphocyte ratio (NLR), and decreased levels of lymphocytes were found in LVO group than that in SVO group, which were correlated with the severity of LVO. In addition, higher percentages of both effector memory (Tem) and central memory (Tcm) T cells, and lower percentage of naïve T cells in CD4+ and CD8+ T cells, were found in LVO group than that in SVO and healthy groups. Moreover, impaired TCR diversity, and different abundances of V-J gene combinations and amino acid sequences, were found in LVO as compared with healthy group, which would be potential biomarkers for LVO diagnosis.DiscussionIn conclusion, AIS with LVO can rapidly induce peripheral immune response, which provides new insight into the understanding of pathophysiology of AIS.